2014
DOI: 10.1371/journal.pone.0103902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the PH1704 Protease from Pyrococcus horikoshii OT3 and the Critical Functions of Tyr120

Abstract: The PH1704 protease from hyperthermophilic archaean Pyrococcus horikoshii OT3 is a member of DJ-1/ThiJ/PfpI superfamily with diverse functional subclasses. The recombinant PH1704 was efficiently purified and was systematically characterized by a combination of substrate specificity analysis, steady-state kinetics study and molecular docking research. The homogeneous protease was obtained as a presumed dodecamer with molecular weight of ∼240 kDa. Iodoacetamide strongly inhibited the peptidase activity, confirmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These enzymes represent a large percentage of the global enzyme market [ 12 , 13 ]. Most proteases from extremophiles belong to the serine type and many of them come from hyperthermophilic archaea belonging to the genera Pyrococcus [ 14 ], Thermococcus [ 15 ], Desulfurococcus [ 16 ], Pyrobaculum [ 17 ], Staphylothermus [ 18 ], and from the thermoacidophilic archaeon Sulfolobus [ 19 ] (see Table 3 ).…”
Section: Proteolytic Enzymes (Ec 34xx)mentioning
confidence: 99%
“…These enzymes represent a large percentage of the global enzyme market [ 12 , 13 ]. Most proteases from extremophiles belong to the serine type and many of them come from hyperthermophilic archaea belonging to the genera Pyrococcus [ 14 ], Thermococcus [ 15 ], Desulfurococcus [ 16 ], Pyrobaculum [ 17 ], Staphylothermus [ 18 ], and from the thermoacidophilic archaeon Sulfolobus [ 19 ] (see Table 3 ).…”
Section: Proteolytic Enzymes (Ec 34xx)mentioning
confidence: 99%
“…Lys43 is also in the immediate neighborhood of the active site, the involvement of which has not been determined; it has been implicated in substrate selection. Tyr120, which was deemed to be important in accessibility to the active site in the P. horikoshii protease (Zhan et al, 2014), is however not present in the protease from T. thioreducens. At position 120 there is a threonine.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent biochemical investigations have indicated that in addition to the catalytic triad, Lys48 and especially Tyr120 are important residues in substrate selection and catalysis. The latter residue has been described as a 'gateway' to the active site (Zhan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A Glu residue, instead of an Asp, completes the catalytic triad (Figs 1b and 2b ). Class-III orthologs PH1704, a protease from Pyrococcus horikoshii [ 39 ], I3RG07, an intracellular protease from Pyrococcus sp . ST04 and and PfpI [ 40 ], an intracellular protease from the hyperthermophilic Sulfolobus solfataricus are devoid of P-domain and the ‘linker region’ ( Fig 2c ).…”
Section: Resultsmentioning
confidence: 99%